The relationship between preoperative serum indirect bilirubin and postoperative delirium in geriatric patients undergoing joint replacement. - Rili Yu; Mi Yang; Juan Chen; Fan Zhang (PLoS ONE)
Background Postoperative delirium (POD) is one of the most common complications in geriatric patients following surgery. Physiological concentration of bilirubin possesses anti-inflammatory, antioxidant and neuroprotective effects, which are important protective mechanisms against POD. This study aimed to explore the relationship between preoperative serum bilirubin and POD in geriatric patients undergoing joint replacement. Methods Geriatric patients who underwent hip or knee joint replacement surgery under intrathecal anesthesia were included. These patients had American Society of Anesthesiologists (ASA) grades I to III. The patients with a history of psychiatric or neurological disorders, infectious diseases or sepsis, hemolytic anemia, liver diseases, performed general anesthesia or intrathecal anesthesia combined with general anesthesia, or insufficient surgical information were excluded. Patients' age, gender, weight, height, ASA classification, liver function and bilirubin within one week before surgery, preoperative Mini-Mental State Examination (MMSE) scores, surgical type, dosage of medications, intraoperative bleeding volume, postoperative average numeric rating scale (NRS) pain scores, the occurrence of POD and Delirium Rating Scale-Revised-98 (DRS-R-98) scores for POD were collected. Results A total of 269 patients were eligible for inclusion in the study, with 23.05% (62/207) exhibiting POD. Patients with POD exhibited higher age and ASA classification, and had lower weight, serum total serum bilirubin (TBIL) and indirect bilirubin (IBIL) within one week before surgery, and preoperative MMSE scores (all p < 0.05). Univariate logistic regression analysis showed that the above variables were correlated with the occurrence of POD (all p < 0.05). Multivariate logistic regression analysis revealed that age was a risk factor (p < 0.001, OR = 1.14, 95% CI [1.07-1.21]), while weight (p = 0.041, OR = 0.96, 95% CI [0.92-0.99]), IBIL levels within one week before surgery (p = 0.012, OR = 0.65, 95% CI [0.47-0.91]) and preoperative MMSE scores (p < 0.001, OR = 0.84, 95% CI [0.78-0.91]) served as protective factors against the occurrence of POD. The serum IBIL concentration within one week before surgery was performed receiver operating characteristic (ROC) curve analysis. The estimated cutoff value for predicting the occurrence of POD was 6.65 μmol/L, and area under the curve (AUC) was 0.63. Patients with preoperative serum IBIL concentration below 6.65 μmol/L had a higher incidence of POD. Conclusion Patients with lower preoperative serum IBIL levels exhibited a higher incidence of POD in geriatric patients undergoing joint replacement. Low serum IBIL was a risk factor and a predictor for the occurrence of POD.